The detrimental effects of Corticosterone administration on post-implantation Embryonic development in mice / Nasibah Azme ... [et al.] - Azme, Nasibah; Mohd Hamim, Rajikin; Mohamed Noor Khan, Nor Ashikin; Abdul Satar, Nuraliza (Universiti Teknologi MARA, Perlis, 2011)
Stress is a common problem encountered by females that could influence fertility. Several stages of normal reproductive process could be disturbed by stress. An increased in corticosterone (CORT) levels is an indication of stress in rodents. Chronic CORT administration in rats has been reported to induce oxidative stress condition and subsequently resulted in tissue damage in the brain. However, reports on the effects of stress or stress hormones in inducing oxidative stress in early pregnancy are still few. Thus, this study aims to investigate the effects of exogenous CORT in inducing oxidative stress in pregnant mice. Mice were given intraperitoneal injection of 5mg/kg body weight (BW), 10mg/kg BW and 20mg/kg BW CORT from day one to day seven of pregnancy. On day seven of pregnancy, mice were subjected to laparotomy to determine the number of implantation sites and blood were taken to analyze the plasma levels of progesterone and malondialdehyde (MDA) following treatment with three different doses of CORT. Litter size were then counted at birth and compared with the number of implantation sites to determine the resorption rate in the treatment and control group. Results showed that lower number of implantation sites (p<0.05), higher resorption rate (p<0.001) and lower plasma progesterone levels (p<0.05) in CORT-treated groups as compared to control. The plasma MDA levels on the other hand were not significantly different in CORT-treated groups as compared to control. This study concluded that CORT administration is detrimental to the post-implantation embryonic development. However, the plasma MDA levels, one of the biomarker for oxidative stress were not changed, thus suggesting that doses and duration of CORT administration in this study is not sufficient to induce oxidative stress condition.